Efficacy of soap and water‐based skin decontamination using in vitro animal models: A systematic review. Issue 6 (23rd December 2021) - Green, Maxwell; Kashetsky, Nadia; Feschuk, Aileen M.; Maibach, Howard I.
Abstract: Water and/or soap and water solutions have historically been used as first‐line decontamination strategies for a wide variety of dermal contaminants from workplace exposure, environmental pesticides, and civilian chemical warfare. Although water and/or soap and water solutions are often considered a gold standard of decontamination, many studies have found other decontamination methods to be superior. This systematic review summarizes the available data on in vitro animal models contaminated with a various chemicals and their decontamination with water and/or soap and water solutions using in vitro animal models. A comprehensive literature search was performed using Concordance, Embase, PubMed, Medline, Web of Science, and Google Scholar to find in vitro animal studies that provided data on dermal decontamination using water and/or soap and water solutions. Five studies were included that analyzed 11 contaminants across two in vitro animal models (rats and pigs). Water alone was used as a decontamination method for 63.6% of the contaminants ( n = 7/11) and water and soap solutions for decontamination in 54.6% of contaminants ( n = 6/11). Water alone provided incomplete contaminant removal of five of seven contaminants studied; soap and water did not show significant difference in decontamination when compared with other solutions for all four contaminants and was superior to water for both contaminants studied. Water and/or soap and water are used as decontamination strategies for a variety of dermal contamination events, but for many contaminants, they do not provide complete contamination when compared with newer decontamination solutions studied with in vitro animal models. Abstract : This systematic review compares water and/or soap and water dermal decontamination to other decontamination solutions using in vitro animal models. Five studies met inclusion criteria that analyzed 11 contaminants across two animal models. Water provided incomplete decontamination for 5/7 contaminants studied. Soap and water was superior to water alone for both contaminants studied and did not show significantly different decontamination efficacy compared with other solutions in 4/4 contaminants. Additional research is needed to continue improving efficacy of dermal decontamination solutions.